Pengaruh Program Rehabilitasi Medik pada Kemandirian Penderita Stroke Iskemik di Rumah Sakit Santa Elisabeth Batam Kota - Kasih Purwati; Yani Christina; Rafida Afra Harlyanti (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background : Stroke is the first cause of disability in the world. The incidence of stroke can cause weakness in daily life. Functional disorders experienced by post-stroke people are one of the factors that are independent in carrying out activities. Efforts to restore limbs is to do rehabilitation. Method : This research method is pre-experimental analytic with a one group pretest posttest study approach which was carried out at Santa Elisabeth Hospital Batam City in December 2021. The sampling technique was total sampling with a sample of 50 respondents.This research was conducted by collecting medical record data. Data analysis using Wilcoxon signed rank test. Results : The results of this study were 50 respondents who took part in the medical rehabilitation program, found 1 respondent who experienced a decrease in the level of independence, there were 23 respondents who experienced an increase in the level of independence, and there were 26 respondents who did not experience a decrease or increase in the level of independence. The results of the bivariate analysis of the Wilcoxon signed rank test showed that there was a significant effect between medical rehabilitation programs on the independence of ischemic stroke patients (p = 0.000). Conclusion : Based on this research, it is concluded that Hᴏ is rejected and Ha is accepted or there is a significant influence between the Medical Rehabilitation Program on the Independence of Stroke Patients at Santa Elisabeth Hospital, Batam City